Analisis Urgensi Perkembangan Pancasila Sebagai Ideologi Bangsa Indonesia - zakiyyah, chilyah (Maliki Interdisciplinary Journal, 2026)
This research discusses the importance of Pancasila and its development as the ideology of the Indonesian nation amidst the dynamics of globalization and digital technological advancement. Using a literature review and comprehensive desk study approach, this research profoundly analyzes Pancasila’s role as the fundamental basis of values governing all aspects of national and state life. The results of the study show that Pancasila remains relevant to face the challenges of the times, especially in maintaining unity and serving as an ethical guideline in national development. However, its implementation still needs to be systematically strengthened through educational reform and a better understanding of Pancasila's values within the community. Overall, this research emphasizes that Pancasila must be actualized to align with current social and global developments. Hence, a deep collective understanding and the maintenance of Pancasila's essential values are fundamental steps for citizens to mitigate threats and foster a responsible, integrated Indonesian society.